Effect of Oral N-Acetylcystein on Galectin-3 in Acute Myocardial Infarction Patients - Jalaludinsyah, Akhmad; Wasyanto, Trisulo; Purwaningtyas, Niniek (Indonesian Journal of Medicine, 2019)
Background: The pathogenesis of heart failure after myocardial infarction is associated with the pathogenesis of cardiac remodeling. Galectin-3 (Gal-3) has a role in the pathophysiology of cardiac remodeling after acute myocardial infarction. N-Acetylcysteine (NAC) can prevent inflammation, remodeling and left ventricular dysfunction, interstitial fibrosis, and improve survival. The purpose of this study was to examine the effect of oral N-Acetylcysteine on Galectin-3 in acute myocardial infarction patients.Subjects and Methods: This was an experimental study with pre and post, single-blind, and randomization methods. The study was conducted at Dr.Moewardi General Hospital Surakarta, Central Java, from June to August 2018. A sample of 29 acute myocardial infarction patients with ST-segment elevation who received fibrinolytic therapy was selected for this study. 14 patients as a control group received standard therapy and 15 patients as intervention group received oral NAC supplementary therapy 600 mg three times daily for three days. The dependent variable was Gal-3 levels. The independent variable was NAC supplementary therapy. The data were analyzed by Mann Whitney test.Results : Gal-3 levels in intervention group (mean= 8.95; SD=1.76) were lowered than the control group (mean= 11.42; SD= 3.76) and it was statistically significant (p= 0.026). Conclusion: Supplementary therapy of NAC 600 mg orally 3 times a day for 3 days can reduce levels of Gal-3 in patients with acute myocardial infarction who receive fibrinolytic therapy.Keywords: galectin-3, n-acetylcysteine, acute myocardial infarction Correspondence: Akhmad Jalaludinsyah. Department of Cardiology and Vascular Medicine, Faculty of Medicine, Universitas Sebelas Maret. Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: dokter.akhmad@gmail.com. Mobile: +6281393098987.Indonesian Journal of Medicine (2019), 4(1): 1-8https://doi.org/10.26911/theijmed.2019.04.01.01